Corruption, political discretion and entrepreneurship. Issue 2 (18th May 2018) - Jiménez, Alfredo; Alon, Ilan
Abstract : Purpose: While common sense suggests that corruption will likely have a negative impact on the economy as it raises the cost of doing business, research on the topic showed inconsistent results (positive, negative and neutral). This paper aims to verify whether corruption has a "grease" or "sand" effect on the wheels of entrepreneurial rates and under which conditions corruption will have stronger or weaker effects. Design/methodology/approach: Using institutional theory as the basis for the hypotheses, generalized least squares estimation is conducted to empirically examine the role of corruption and political discretion in entrepreneurship in a sample of 93 countries. Findings: Countries with higher levels of corruption are associated with lower levels of firm creation. However, this negative effect of corruption is weaker when there are higher levels of political discretion. Originality/value: This is the first evaluation of the moderating effect of political discretion on the negative impact of corruption on entrepreneurship.